Breast cancer immunophenotype and its relationship with haematopoiesis - Denis A. Ryabchikov (IP Habib O.N., 2021)
Background. The applying of immunotherapeutic approaches in cancer treatment requires a deep and comprehensive understanding of the tumor biological characteristics. In this regard, the study of the tumor immunophenotype is one of the leading scientific directions. The major histocompatibility complex molecules are considered to be the promising markers of the immunotherapy effectiveness prediciton.